An alternative proof of hill's criterion of freeness for abelian groups (2010)
In this note we provide a different proof of Hill's criteria of freeness for abelian groups. Our proof hinges on the construction of suitable $G(\aleph_0)$-families of subgroups of the links in Hill's theorem and, ultimately, on the construction of such a family of pure subgroups of the group itself.